Antimycobacterial Activities of Isoxyl and New Derivatives through the Inhibition of Mycolic Acid Synthesis - Phetsuksiri, Benjawan (American Society for Microbiology, 1999)
Isoxyl (ISO), a thiourea (thiocarlide; 4,4′-diisoamyloxythiocarbanilide), demonstrated potent activity against Mycobacterium tuberculosis H37Rv (MIC, 2.5 μg/ml), Mycobacterium bovis BCG (MIC, 0.5 μg/ml), Mycobacterium avium (MIC, 2.0 μg/ml), and Mycobacterium aurum A+ (MIC, 2.0 μg/ml), resulting in complete inhibition of mycobacteria grown on solid media. Importantly, a panel of clinical isolates of M. tuberculosis from different geographical areas with various drug resistance patterns were all sensitive to ISO in the range of 1 to 10 μg/ml. In a murine macrophage model, ISO exhibited bactericidal killing of viable intracellular M. tuberculosis in a dose-dependent manner (0.05 to 2.50 μg/ml). The selective action of ISO on mycolic acid synthesis was studied through the use of [1,2-(14)C]acetate labeling of M. tuberculosis H37Rv, M. bovis BCG, and M. aurum A+. At its MIC for M. tuberculosis, ISO inhibited the synthesis of both fatty acids and mycolic acids (α-mycolates by 91.6%, methoxymycolates by 94.3%, and ketomycolates by 91.1%); at its MIC in M. bovis BCG, ISO inhibited the synthesis of α-mycolates by 87.2% and that of ketomycolates by 88.5%; and the corresponding inhibitions for M. aurum A+ were 87.1% for α-mycolates, 87.2% for ketomycolates, and 86.5% for the wax-ester mycolates. A comparison with isoniazid (INH) and ethionamide (ETH) demonstrated marked similarity in action, i.e., inhibition of the synthesis of all kinds of mycolic acids. However, unlike INH and ETH, ISO also inhibited the synthesis of shorter-chain fatty acids. ISO showed no acute toxicity against primary macrophage cell cultures as demonstrated by diminution of redox activity. A homologous series of ISO derivatives were synthesized. Most derivatives were as effective or more effective than the parent compound in the agar proportion assay. Thus, these thioureas, like INH and ETH, specifically inhibit mycolic acid synthesis and show promise in counteracting a wide variety of drug-sensitive and -resistant strains of M. tuberculosis.